Synthesis and ring openings of cinnamate-derived N-unfunctionalised aziridines - Armstrong, Alan; Ferguson, Alexandra (Beilstein Journal of Organic Chemistry, 2012)
tert-Butyl cinnamates are aziridinated with high trans-selectivity by an N–N ylide generated in situ from N-methylmorpholine and O-diphenylphosphinyl hydroxylamine. The resulting N-unfunctionalised aziridines are shown to be versatile synthetic building blocks that undergo highly selective ring-opening reactions with a wide range of nucleophiles.
Keywords: amino acids; aziridination; organocatalysis; ring opening; stereoselectivity